Crane Derrick Maintenance Strategy for Smooth Loading and Unloading on MV. Blossom Pescadores - Pradipa Akbar Gibrani; Makmur Makmur; Rajuddin Rajuddin (Darul Yasin Al Sys, 2026)
The smoothness of loading and unloading operations is strongly influenced by the readiness of onboard cargo-handling equipment, particularly crane derrick systems on general cargo vessels. Although previous studies have examined cargo-handling equipment and shipboard maintenance, research specifically addressing crane derrick maintenance strategies using weighted SWOT analysis remains limited. This study aims to analyze the maintenance strategy for crane derrick cargo-handling equipment to support loading and unloading operations on MV. Blossom Pescadores. A qualitative descriptive approach with a case study design was employed. Data were collected through observation, interviews, documentation, and literature study during sea practice on board the vessel. The data were analyzed using SWOT analysis by identifying internal factors, comprising strengths and weaknesses, and external factors, comprising opportunities and threats, which were then formulated into IFAS and EFAS matrices. The findings indicate that crane derrick maintenance on board was still constrained by internal weaknesses, particularly unstructured maintenance schedules, limited operational supervision, and incomplete spare part availability. However, external opportunities remained available through the continued demand for general cargo vessels and knowledge transfer from experienced officers to junior crew members. The SWOT analysis positioned the maintenance strategy in the WO quadrant, indicating that available opportunities should be used to overcome internal weaknesses. This study concludes that structured maintenance schedules, regular wire rope inspection, stronger operational supervision, improved spare part management, and crew competence development are essential to maintain crane derrick readiness. The findings provide practical implications for deck officers and shipping companies in improving the safety, smoothness, and efficiency of loading and unloading operations.